Major Human Cytomegalovirus Structural Protein pp65 (ppUL83) Prevents Interferon Response Factor 3 Activation in the Interferon Response - Abate, Davide A. (American Society for Microbiology, 2004)
We have identified a cytomegalovirus virion protein capable of modulating the rapid induction of an interferon-like response in cells that follows virus binding and penetration. Functional genomics revealed a role for the major cytomegalovirus structural protein, pp65 (ppUL83), in counteracting this response. The underlying mechanism involves a differential impact of this structural protein on the regulation of interferon response factor 3 (IRF-3). In contrast, NF-κB is activated independent of pp65, and neither STAT1 nor STAT3 becomes activated by either virus. pp65 is sufficient to prevent the activation of IRF-3 when introduced alone into cells. pp65 acts by inhibiting nuclear accumulation of IRF-3 and is associated with a reduced IRF-3 phosphorylation state. Thus, this investigation shows that the major structural protein of cytomegalovirus is committed to the modulation of the IRF-3 response, a primary mediator of the type I interferon response. By subverting IRF-3, the virus escapes throwing a central alarm devoted to both immediate antiviral control and regulation of the immune response.